Aplicación de la terapia respiratoria y su impacto en la evolución del enfisema pulmonar en adultos mayoresde la comunidad Malvinas, cantón Ventanas los ríos, período septiembre 2017 a febrero 2018 - Merelo García, Alison Elber (2018)
Introduction: It is necessary to contribute to health by using investigative works that are attached to several problems, which is why this research contributes significantly in the area of respiratory therapy by developing a viable alternative to the problem, such as pulmonary emphysema. Objective: To identify how the application of respiratory therapy is related to its impact on the evolution of pulmonary emphysema in older adults of the Malvinas community, Cantón Ventanas Los Ríos period September 2017 to February 2018. Methodology: The methods that were applied were the deductive and the inductive method. The sample was of 35 people by random sampling by non-probabilistic conglomerate. Observation techniques, unstructured interviews and surveys to collect information were also applied. Results: The age at which it begins to have respiratory problems according to the survey we obtained that 57%, that is, the majority began between 60 to 70 years. 67% of older adults do not know what respiratory therapy is. However, 100% of the respondents felt that they would like to attend informative talks on the application of respiratory therapy in pulmonary emphysema. Conclusions: Older adults are unaware of the effective treatments offered by respiratory therapy to improve health.